Explaining Central Bank Trust in an Inflation Targeting Country: The Case of the Reserve Bank of New Zealand - Bernd Hayo; Florian Neumeier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Employing data from a representative population survey conducted in New Zealand in 2016, this paper examines factors that influence, or are at least associated with, public trust in the Reserve Bank of New Zealand (RBNZ). The large number of specifically designed questions allows studying the relationship between six dimensions and RBNZ trust: (i) economic situation, (ii) monetary policy knowledge, (iii) nonspecific trust, (iv) interest and information search, (v) politicians and government, and (vi) socio-demographic indicators. Using ordered logit models, we find that at least one indicator from each of these six dimensions has a statistically significant conditional correlation with individuals' trust in RBNZ. Satisfaction with own financial situation, objective knowledge about the RBNZ's main policy objective, responsibility for interest rate setting, subjective knowledge about inflation, trust in government institutions, desire to be informed about RBNZ, age, and full-time selfemployment have a positive relationship with RBNZ trust. The reverse is found for respondents who do not keep up with RBNZ and believe that politicians are long-term oriented. In terms of economic relevance, institutional trust has the largest single impact on RBNZ trust and the subjective and objective knowledge indicators show a strong combined influence.
Keywords: E52; E58; Z10; 330; Central Bank Trust; Survey; Public Attitudes; Reserve Bank of New Zealand; Monetary Policy